Inovasi dan Kinerja Pemerintah - Ervina Yunita (Puslatbang KHAN, 2017)
Innovation is able to boost government’s performance. It encourages government to optimize the resources in order to increase the quality and quantity of pubic services. However, performance improvement is highly dependent on agency capabilities using built applications. Therefore, this study aims to see the improvement of agency performance with the innovation. This study uses quantitative and qualitative approaches by using questionnaires and in-depth interviews. The results of this study indicate that as many as 28.57 percent of respondents said there is a very high increase in outcome and output agencies with the innovation. However, there are still about 27.38 percent indicating a low increase post utilization of innovation. The obstacles faced are the quality of innovation built and the capability of utilization and commitment of the utilization of innovation. Therefore, the need for optimization of innovation in order to improve the performance of agencies. In addition, the development of innovation must also adjust to the needs of agencies so as to be optimized in solving problems and improve agency performance.